Компетентнісний вимір музейної освіти студентської молоді - Вербицька, Поліна; Verbytska, Polina (Східноєвропейський національний університет імені Лесі Українки, 2015)
У сучасних соціокультурних умовах під час формування змісту музейної освіти важливий розвиток її компетентнісного спрямування, що передбачає формування соціокультурної компетентності студентів, орієнтацію особистості на засвоєння цінностей і досягнень багатокультурної спадщини, позитивне сприйняття та відтворення загальноприйнятних соціокультурних норм, формування на цій основі соціально-комунікативної здатності конструктивної суспільної взаємодії. В современных социокультурных условиях при формировании содержания музейного образования в высшем учебном заведении важным есть развитие ее компетентностной направленности, что предусматривает формирование социокультурной компетентности личности, ориентацию на усвоение ценностей и достижений поликультурного наследия, позитивное восприятие и воспроизводство общепринятых социокультурных норм, формирование на этой основе социокультурной способности к конструктивному общественному взаимодействию.In modern sociocultural conditions by formulating the content of museum education it higher educational establishment is important to develop sociocultural competences of students, which foresees individual’s orientation in familiarization of multicultural heritage values and achievements of world cultural heritage, positive perception and realization sociocultural norms and forming on this basis socio-cultural ability to constructive social interaction. The main principals of it realization is the creation of conditions for development the abilities of students for social communication, critical thinking and responsible participation in multicultural society, using of innovative educational technologies and forms of education. Museum education of students is based on set of values, which through the culture and traditions determine the direction of teaching efforts in the process of establishment of socio-cultural features of individuals. The result of the realization of competence dimension of museum education of students should become the formation of socio-cultural competences as the complex of basic socio-cultural skills, which provide the preparation of youth for professional self-realization and responsible social communication in multicultural society.
Competent Dimension of Museum Education of Students.
Keywords: студентська молодь, музейна освіта, соціокультурна компетентність, міжкультурний діалог.; студенческая молодежь, музейное образование, социокультурная компетентность, межкультурный диалог.; students youth, museum education, sociocultural competence, intercultural dialog.